PRO KONTRA IMPLEMENTASI PERDA SYARIAH (Tinjauan Elemen Masyarakat) - Suharso, Pudjo (Islamic University of Indonesia, 2006)
Since the beginning of reformation era 1998, substancially and siqnificantly there is the changing of Indonesian political system. One of the changing is the decentralization based on the Act No. 22 year 1999 and then it is reformed by the Act No. 32 year 2005. The decentralization political system to place local authonomy as new basic of the local governance. In this era emerging several local acts, including the local acts beased on Islamic Shariâah. The local acts based on Islamic Shariâah invites pros and conts. Hence, the central government tries to conduct judicial review toward 12000 local acts. Kata kunci: perda, review, desentralisasi, otonomi, dan pemda.